Implementation of Agile Governance In Optimizing The Potential of Sekapuk Village, Gresik District - Muhammad Chasan Amruloh; Rumanintya Lisaria Putri (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2023)
Sekapuk Village, Ujungpangkah District, Gresik Regency is the poorest village that has succeeded in becoming a billionaire village through the management of BUMDesa for setigi tourism. This success was able to increase the original income of the village and the economy of the community. This research will validate the application of agile governance in Sekapuk Village to be able to find out the application that has been carried out by the village government in sustainable development. This study aims to describe the application of agile governance in the management of setigi tourism which was previously a former limestone mine excavation and landfill into a tourist attraction of high economic value. This research uses a descriptive type of qualitative research with data collection techniques carried out through observation techniques, interviews, documentation and previous research. Keywords: Sekapuk Village, Village Owned Enterprises, Agile Governance, Setigi Tourism, Tourism. The results showed that BUMDesa Sekapuk has applied the principle of agile governance in managing setigi tourism properly. First, good enough governance, setigi tourism management has included the division of labor, management structure, and has the purpose of tourism development. Second, business driven, it is shown by the sale of tourist shares to the public. Third, human focused, the contribution of the community to the sale of shares in the development of setigi tourism. Fourth, based on quick wins, there is an increase in the original income of the village every year.